Effective practices of international volunteering for health: perspectives from partner organizations - Benjamin J. Lough; Rebecca Tiessen; Judith N. Lasker (BMC, 2018)
Abstract Background The demand for international volunteer experiences to promote global health and nutrition is increasing and numerous studies have documented the experiences of the international volunteers who travel abroad; however, little is known about effective practices from the perspective of partner organizations. This study aims to understand how variables such as the skill-level of volunteers, the duration of service, cultural and language training, and other key variables affect partner organizations' perceptions of volunteer effectiveness at promoting healthcare and nutrition. Method This study used a cross-sectional design to survey a convenience sample of 288 volunteer partner organizations located in 68 countries. Principle components analyses and manual coding of cases resulted in a categorization of five generalized types of international volunteering. Differences among these types were compared by the duration of service, skill-level of volunteers, and the volunteers' perceived fit with organizational needs. In addition, a multivariate ordinary least square regression tested associations between nine different characteristics/activities and the volunteers' perceived effectiveness at promoting healthcare and nutrition. Results Partner organizations viewed highly-skilled volunteers serving for a short-term abroad as the most effective at promoting healthcare and nutrition in their organizations, followed by slightly less-skilled long-term volunteers. The greatest amount of variance in perceived effectiveness was volunteers' ability to speak the local language, followed by their skill level and the duration of service abroad. In addition, volunteer training in community development principles and practices was significantly related to perceived effectiveness. Conclusion The perceptions of effective healthcare promotion identified by partner organizations suggest that program and volunteer characteristics need to be carefully considered when deciding on methods of volunteer preparation and engagement. By better integrating evidence-based practices into their program models, international volunteer cooperation organizations can greatly strengthen their efforts to promote more effective and valuable healthcare and nutrition interventions in partner communities.